An Evaluation of Wound Healing Efficacy of a Film Dressing Made from Polymer-integrated Amnion Membrane. (1st October 2020) - Wang, Bo; Li, Wuwei; Harrison, Justin
ABSTRACT: A film dressing is an easy and common wound management, which is flexible to cover many types of superficial injuries. In a recent study, we developed a scaffold from poly (1, 8-octanediolco-citrate) incorporated decellularized amnion membrane (DAM-POC). The DAM-POC scaffold was biocompatible and could enhance soft and hard tissue regeneration when applied to repair the cleft palate in rat. The efficacy of the DAM-POC scaffold in oral repair had led us to hypothesize that it could be employed extensively in the medical field as a wound dressing. This study aimed to investigate the feasibility and efficacy of the DAM-POC scaffold as a film dressing in accelerating wound healing when applied in multiple tissue injuries. Our results demonstrated that both the DAM and DAM-POC scaffolds were biocompatible and anti-adhesive without causing severe foreign body reactions when covering wounds in abdominal wall, back muscle, tibia bone, and liver. In addition, the DAM-POC scaffold was superior to the DAM scaffold in reducing inflammation, preventing fibrosis, and regenerating tissues. In conclusion, the DAM-POC scaffold might potentially be adopted as a film dressing in a wide range of therapeutic applications and healing situations to protect the damaged tissues from the external environment and prevent infections.